The politics of transindividuality - Read, Jason (Historical materialism book series ;, 2016)
The Politics of Transindividuality re-examines social relations and subjectivity through the concept of transindividuality. Transindividuality is understood as the mutual constitution of individuality and collectivity, and as such it intersects with politics and economics, philosophical speculation and political practice. While the term transindividuality is drawn from the work of Gilbert Simondon, this book views it broadly, examining such canonical figures as Spinoza, Hegel, and Marx, as well as contemporary debates involving Etienne Balibar, Bernard Stiegler, and Paolo Virno. Through these intersecting aspects and interpretations of transindividuality the book proposes to examine anew the intersection of politics and economics through their mutual constitution of affects, imagination, and subjectivity.